Samarium(II) iodide-mediated deoxygenative debromination of α-bromo-β-hydroxy (acetoxy) phenyl sulfones: Synthesis of α,β-unsaturated sulfones - Vichai Reutrakul (2018)
Deoxygenative debromination of α-bromo-β-hydroxy (acetoxy) phenyl sulfones with samarium(II) iodide led to substituted α,β-unsaturated sulfones in good to excellent yields. The E-isomer is the major product. A possible mechanism via an α-sulfonyl radical pathway is proposed. © 2002 Elsevier Science Ltd. All rights reserved.